Assistierter Suizid Zum gesellschaftlichen Diskurs und seinem Einfluss auf betagte und hochbetagte Menschen - Kautz, Heike (Young Academics: Perspektiven auf Pflege, 2023)
The social discourse on assisted suicide for the elderly is extremely complex and deals with issues such as ethics and the culture of dying as well as images of old age. It was strongly influenced by the ruling of the Federal Constitutional Court in 2020, which classified the ban on assisted suicide as unconstitutional. Heike Kautz attributes this court assessment to strong individualisation and the decline of solidary community. However, this ruling could strongly normalise assisted suicide and the elderly and very old could feel pressured to die in this way. The author therefore pleads for a reflected professional discourse.